Quantifying spatial dependencies, trade‐offs and uncertainty in bioenergy costs: an Australian case study (2) – National supply curves. (10th June 2014) - Brinsmead, Thomas S.; Herr, Alexander; O'Connell, Deborah A.
Abstract A biophysically constrained economic analysis of several alternative biofuel production pathways develops upper and lower bounds on national supply cost curves, taking into account implicit spatial dependencies and trade‐offs. As well as land (and sea) transport suitable biofuels, we also consider electricity and aviation biofuels. One feedstock (crop residues from grains) and five bioenergy pathways illustrate this approach for Australia. The methods are, however, applicable to any feedstock, bioenergy technology, region, or scale. Biofuel production costs, dependent on the spatial concentration of available feedstock, are derived in a companion paper by selecting a cost minimizing production scale. Lower concentrations imply smaller processing plants and greater collection areas and costs. Any candidate production plant location can have a collection area that approximates the least cost for its average spatial concentration, because feedstock concentration varies only modestly within cost minimizing area scales. A set of plant locations, scales, and near to least‐cost collection areas, is found that collectively service all the available residue feedstock using Australian data. This generates upper and lower bounds on nationally aggregated supply cost curves. The sizing of biofuel facilities will be also affected by investment scale commercial considerations, including the reliability of feedstock and investor appetite for risk: these are discussed qualitatively. © 2014 Society of Chemical Industry and John Wiley & Sons, Ltd